2011
DOI: 10.1002/pmic.201100186
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of biological protein–protein interactions using atom‐type and amino acid properties

Abstract: Identification and analysis of types of biological protein-protein interactions and their interfaces to predict obligate and non-obligate complexes is a problem that has drawn the attention of the research community in the past few years. In this paper, we propose a prediction approach to predict these two types of complexes. We use desolvation energies - amino acid and atom type - of the residues present in the interface. The prediction is performed via two state-of-the-art classification techniques, namely l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 46 publications
(57 reference statements)
0
19
0
Order By: Relevance
“…We compare our approach with prediction of obligate and non-obligate using desolvation energies as properties [7]. Their work was based on the ZH and MW datasets.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We compare our approach with prediction of obligate and non-obligate using desolvation energies as properties [7]. Their work was based on the ZH and MW datasets.…”
Section: Resultsmentioning
confidence: 99%
“…A model that uses solvent accessible surface area and other interface properties for prediction of types (obligate and nonobligate) was reported in [8]. A very recent work presented in [7] shows the use of desolvation energies to predict obligate and non-obligate complexes using SVM and linear dimensionality reduction (LDR).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…In addition, other properties have been used for prediction of PPIs, such as analysis of solvent accessibility [6], geometry, hydrophobicity, sequence-based features, and desolvation energy [7]. Based on interface properties such as interface area and ratio of area [6], Zhu et al predicted biological and crystal packing interactions using a support vector machine (SVM).…”
Section: Introductionmentioning
confidence: 99%
“…Features are the observed properties of each sample that are used for prediction. Some studies on PPIs consider a wide range of features for predicting obligate and non-obligate complexes, including solvent accessibility (Shanahan and Thornton 2005;Zhu et al 2006), geometry (Lawrence and Colman 1993), hydrophobicity (Young 1994;Glaser et al 2001), sequencebased features (Mintseris and Weng 2003), desolvation energy Hall et al 2012;Rueda et al 2010a, b;Aziz et al 2011) and, more recently, electrostatic energies (Vasudev and Rueda 2012). In this study, we use desolvation energies, which have been shown to be very efficient for PPI prediction (Rueda et al 2010a, b).…”
Section: Introductionmentioning
confidence: 99%